The Evolution of Consumption in the Digital Era: An Islamic Economic Perspective from Traditional Markets to Modern Markets - saifuddin saifuddin; Zulfian Aldiansyah; Sujiono (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Economic growth in various sectors, such as industry, production, and modern markets, has undergone changes as a result of advanced economic growth, particularly in large cities. Conversely, the shift from traditional lifestyles to modern lifestyles has led to changes in consumer spending patterns. The goal of this study is to determine the impact of modern market development on people's economies and lifestyles. The second factor that most influences consumers' decisions to shop at modern markets rather than traditional markets is the factor that most affects their decision to shop at modern markets. The research method used in this study is qualitative. Research findings indicate that consumer behavior has shifted from traditional markets to modern markets for several reasons, one of which is that modern markets offer convenient facilities.